Pengaruh Latihan Permainan Target Terhadap Kemampuan Akurasi Smash Bola Voli Siswa di SMKN 2 Makassar - Akbar, Muh. Ainul; hasmyati, Hasmyati; Juhanis, Juhanis; Hasan, Muh. Said; Hudain, Muh. Adnan (UNIVERSITAS NEGERI MAKASSSAR, 2025)
This study aims to determine the effect of target game training on the accuracy of students' bolavoli smash at SMKN 2 Makassar. The sample in this study amounted to 30 people. The research instruments used in this study are: 1. Bolavoli field, 2. Ball 3. Net 4. Scoring sheet to record test results. The research method used is a pseudo-experiment research method, namely research that compares the treatment group with the control group. Technically measuring the results of these instruments carried out on all samples through pretest and posttest, then normality test, homogeneity test, and paired sample T-Test using SPSS application. Based on the results of data analysis, the researchers concluded that: 1. There is a significant effect of the treatment group given target game training on the accuracy of bolavoli smash by students at SMKN 2 Makassar. 2. There is no significant effect of the control group that is not given target game training on the accuracy of volleyball smash by students at SMKN 2 Makassar.